Determinan of Factors Associated with Maternity Emergency of Premature Rupture of Membranes: A Literature Review - Ayu Anggraini, Tyas; Lutfiyati, Afi (MEDIA ILMU KESEHATAN, 2023)
Background: Premature Rupture of Membranes (PROM) is an emergency during to the puerperium which cause serious problems for the mother and fetus. Objective: To identify the determinants factors associated with PROM in pregnant women. Methods: A systematic review of the literature on articles published in the 2017-2022 timeframe. The journal was obtained through 8 databases (Google scholar, PubMed, Garuda Portal, Science Direct, Proquest, Crossref, National Library, Scopus) using "Maternity Emergency" AND "Premature rupture of membranes". Results: The results of the study search found 1,413 articles which seven articles were selected and reviewed. The results show that the factors associated with PROM included parity (p=0.034; 0.034; 0.001), maternal age (p=0.018; 0.018; 0.063), exposure to cigarette smoke (p=0.044), sexual pattern (p=0.008), frequency of ANC (p=0.001), anemia (p=0.001), history of cervical conization (p=0.010), cervical length <25 mm at week 28 (p=0.009), negative lactobacillus (p=0.030), and second trimester bleeding (p=0.020). Conclusion: The most dominant factor associated with the incidence of PROM were history of cervical conization.